An assessment of risk management practices and travel-related perceptions among Thai tourist scuba divers in Phuket - Panyaporn Jiamsajjamongkol (Prince of Songkla University, 2023)
Master of Business Administration (Hospitality and Tourism Management (International Program)), 2022